2020
DOI: 10.1111/dme.14449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of routine clinic measurement of serum C‐peptide in people with a clinician‐diagnosis of type 1 diabetes

Abstract: The aim of this study was to determine the impact of the routine use of serum C-peptide in an out-patient clinic setting on individuals with a cliniciandiagnosis of type 1 diabetes. Methods: In this single-centre study, individuals with type 1 diabetes of at least 3 years duration were offered random serum C-peptide testing at routine clinic review. A C-peptide ≥200 pmol/L prompted further evaluation of the individual using a diagnostic algorithm that included measurement of islet cell antibodies and genetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
4
37
0
Order By: Relevance
“…As expected, this was lower in young-adults but still 45% of those negative for all islet autoantibodies and 6% of the entire age group. Our results are supported by another recent study which used C-peptide at over 3 years duration to define type 1 diabetes and found a similar rate of misclassification (20). Foteinopoulou et.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As expected, this was lower in young-adults but still 45% of those negative for all islet autoantibodies and 6% of the entire age group. Our results are supported by another recent study which used C-peptide at over 3 years duration to define type 1 diabetes and found a similar rate of misclassification (20). Foteinopoulou et.…”
Section: Discussionsupporting
confidence: 89%
“…Foteinopoulou et. al showed the presence of non-type 1 diabetes in 14% and 7% of all individuals who were clinically thought to have type 1 diabetes aged ≥30 years and 18-30 years respectively at diagnosis (20). All the misclassifications in their study were seen in antibody negative participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study enabled reclassification of diabetes type in 6.8% of patients; however, insulin treatment was only stopped in 1.5% of the patients studied. 10 The American Diabetes Association (ADA) standards of medical care for diagnosis and classification of diabetes type acknowledge that some individuals cannot be diagnosed with diabetes type at the time of diagnosis and that time may be required to appreciate beta cell deficiency. These standards suggest measuring islet autoantibodies in adults presenting with diabetes who do not have any traditional risk factors for type 2 diabetes such as obesity, hypertension, dyslipidaemia or a family history of type 2 diabetes, as would have been applicable for the case reported here at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes subtype identification can be challenging for clinicians, so the publication of a stratified diagnostic pathway for diabetes subtype assignment is especially welcome. 10 The pathway, which includes the assessment of c-peptide, auto-antibodies and genetics where appropriate, can be implemented in any clinic and is effective in reassigning diagnoses, changing treatment and identifying families where genetic counselling may be helpful. For more discussion of this, head to the Diabetic Medicine podcast homepage where I interview the lead investigator (www.…”
mentioning
confidence: 99%